Aspectos comportamentais, bioquímicos e moleculares implicados no papel do magnésio nos distúrbios motores induzidos experimentalmente em ratos - Kronbauer, Maikel (2019)
The chronic use of typical antipsychotics has been related to movement disorders development, which are manifested by repetitive, tremors and tardive dyskinesias, manifestations that can reach disabling levels and impair the pharmacological treatment of the original pathology. The aim of the present study was to evaluate magnesium supplementation (Mg; 40 mg / kg, oral, once daily) in prevention (28 days before) and reversion (12 days after), as well as in concomitant supplementation, on haloperidol-induced orofacial dyskinesia (OD) (12 mg / kg; im, once weekly for 4 weeks) in rats. The results showed that the Mg supplementation before, after and concomitant to HAL administration, prevented, reversed and protected from the high vacuous chewing movements frequency (VCM) and cataplepsy. Mg supplementation: i) prevented the generation of reactive species (RS) in cortex and substantias nigra (SN), and reduced the levels of carbonylated proteins (CP) in all evaluated brain areas; ii) reversed RE generation induced by HAL in the cortex and striatum and decreased CP levels in both SN and striatum; iii) prevented RS generation the cortex, striatum and SN, as well as the increased CP levels in SN. From these results, a comparative study between Mg supplementation and nifedipine administration (NIF-10mg / kg / ml, orally, once daily) on the movement disorders induced by HAL in rats was performed sequentially, in order to determine if Mg action is similar to NIF. Both Mg and NIF reduced HAL induced OD. Also, while HAL increased Ca2 + -ATPase activity in the striatum, Mg supplementation reversed it. In the cortex, both Mg and NIF reduced this activity. The immunoreactivity of dopaminergic D1 and D2 receptors and the glutamatergic receptor NMDA were modified in different ways by HAL in the cortex, striatum and SN areas, as well as by the treatments. Of particular importance, was observed the increased immunoreactivity of NMDA receptors in all brain areas being reduced by Mg or NIF in all brain areas analyzed. These findings allow us to propose that Mg may be useful in preventing and minimizing movement disorders induced by classical antipsychotics such as HAL, whose molecular mechanism seems to be involved with a significant and possibly more consistent calcium channel block activity, provided that the group of animals treated with NIF showed less expressive responses when compared to the group treated with Mg. Taken together, the results presented in these studies indicate that Mg supplementation is able to prevent or ameliorate extrapyramidal motor disorders whose mechanism of action seems to be involved in calcium channel blockade. These disorders are often related to chronic antipsychotic treatment, so far there is no effective preventative treatment. Mg supplementation, which is a bivalent cation with low systemic toxicity and low cost, may be an accessible and effective alternative for patients undergoing neuroleptic treatment.